Outsourcing: A Potential Shock Absorber for the Hotels in Bono and Ahafo Regions (International Journal of Technology and Management Research, 2020)
This study assesses the effect of outsourcing on organisational performance of hotels in Bono and Ahafo Regions. The study adopted quantitative method using descriptive survey. Forty (40) managerial staffs were purposively and randomly sampled. The primary data was gathered using questionnaire while secondary data were obtained from the list of registered hotels from Ghana Tourism Authority and validated through peer review. Descriptive and inferential statistics were used to analyses the data gathered. The study found thatoutsourcing had contributed to increase productivity, profits, encourages employee innovation, maintains competitiveness in the market, allows hotel to focus on core areas and provides faster and quality service to customers. However, the study revealed some challenges that hotels operators face as a result of outsourcing some of their operations such as exposure of itself to operational risks; it affects the continuity of skill supply and the retention of in-house knowledge and expertise, and it causes disruption to the continuity of the services. It is recommended that, hotels should put in place risk control measures so that failures on the part of the outsourced agencies are curtailed.
Keywords: Outsourcing; absorber; hotels; Bono Region; Ahafo Region